Mnenje slovenskih in evropskih psihologov o uporabi psiholoških testov danes in pred desetimi leti - Boben, Dušica (Psihološka obzorja (Ljubljana), 2011)
In 1999, the EFPA Standing Committee on Test and Testing created a questionnaire in order to know the opinions of professional psychologists on testing practices. The questionnaire involved items relating to: knowledge and competencies, regulations on test and testing, concern over incorrect test use and assessment, appreciation of tests and testing etc. In 2009 the survey was repeated with adapted questionnaire and Slovenian psychologists took an active part in it. The article presents Slovenian results from current survey, a comparison with results from other European countries and with Slovenian results in 1999.
Keywords: psihološki testi; psychological tests; attitudes; psihologi; psychologists; stališča; Slovenia; mnenja; Europe; Slovenija; Evropa